PENGENALAN AKUNTANSI DASAR DALAM MENCATAT DAN MENILAI PERSEDIAAN PERUSAHAAN DAGANG KEPADA MURID SMA TARSISIUS 1 - Ivonne Patricia; Widyasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
In the current era of globalization, knowledge of accounting is crucial for high school students as an initial foundation to comprehend the business world. Despite the integration of accounting into the high school economics curriculum, students' awareness and interest in this subject remain limited, particularly regarding the recording and valuation of inventory for trade companies. Therefore, seeks to improve the comprehension of SMA Tarsisius 1 students about fundamental accounting concepts related to recording and valuing inventory. This research will be conducted through a series of instructional activities, focusing on interactive and applicative teaching methods. Students will be guided to understand the steps in recording and valuing inventory, delve into basic accounting concepts, and observe their real-world applications in the context of trade companies. The proposed teaching methods include lectures, group discussions, and hands-on practices using case studies of leading trade companies. The activities are planned to take place offline at SMA Tarsisius 1, Jakarta, on October 18th, 2023. Throughout the activities, we will present the material with a more contextual and engaging approach, utilizing interactive learning media and real case studies. Additionally, guide modules and practice questions will be provided to reinforce student understanding. Expected outcomes of this activity include increased student interest in accounting, a better understanding of inventory recording and valuation, and a more positive outlook on potential careers in the accounting field. The success of this activity is anticipated to assist students in making more informed decisions regarding their choice of study at the university level, with the hope of encouraging more students to select accounting as their major.